Correlation between Mandibular third Molar Impactions and the Skeletal Face Type - Hafsa Gul, Rubbab Zahra, Nadia Bhutta, Varda Jalil, Shahlisa Hameedi, Khurram Shahzad, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To investigate the correlation between mandibular third molar impactions and the skeletal face type both sagittally and vertically. Study design: Cross-sectional study Place and duration of study: Avicenna dental hospital, Lahore from July 2019 to September 2021. Methodology: Pre-treatment records of 135 patients visiting the Orthodontics department of Avicenna Dental Hospital, including history, clinical examination, photos, study casts and radiographs were retrospectively studied to determine the skeletal face type and status of mandibular third molars. Relationship of skeletal face type was correlated with the impacted third molars. Results: Mean age of the patients was 22 years with more (67%) patients being females. Mandibular third molar impactions were 39.58% in skeletal Class I, 57.53% in Class II and 35.71% in Class III respectively. Both mandibular third molars were found impacted in 64.28% dolicofacial, 53.96% mesofacial and 53.33% brachyfacial patients. Conclusion: Mandibular third molars are impacted in many patients reporting to Orthodontics department. Both mandibular third molars were significantly more impacted in dolicofacial skeletal face type and skeletal Class II individuals. Keywords: Skeletal face type, dolicofacial, brachyfacial, mesofacial, growth pattern, molar impactions, Orthodontics.